Routledge handbook on international economic law - Vadi, Valentina; Collins, David, 1975- (Routledge handbooks in law, 2026)
"This book presents a broad, clear, and accessible overview of international economic law. It consists of contributions from leading scholars and rising stars in the field from across the globe. The Handbook comprises five main parts. Part One deals with the history and theory of the discipline. Parts Two, Three, and Four deal with the main substantive areas of international economic law: international trade law, international investment law, and international financial and monetary law. Part Five explores the link between international economic law and other international legal regimes, such as environmental law and human rights law, highlighting areas where tensions may occur between economic liberalization, sovereignty, and other concerns. The Handbook investigates international economic law's theory, policy, and practice from various perspectives. Its 31 chapters highlights central themes that have driven the development of this dynamic subject, reflecting the field as it exists now, while also serving as a point of departure for future studies. The book will provide a solid resource for scholars, students, policymakers, and practitioners in international law, international relations, political science, and economics"--